2016
DOI: 10.1364/oe.24.028905
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optically spectrum narrowed, multiline intracavity optical parametric oscillators

Abstract: We report on the first building of an active spectral narrowing mechanism in a pulsed, multiline optical parametric oscillator (OPO) based on a novel aperiodically poled lithium niobate (APPLN) device constructed using the aperiodic optical superlattice technique. The APPLN device functions simultaneously in the system as a multi-channel optical parametric down converter (OPDC) and an electro-optic (EO) gain spectral filter working on the corresponding (multiple) signal bands. When the APPLN OPO was installed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It arouses our interest. As early as 1990, the sub-natural linewidth in the spontaneous emission spectrum of a threelevel atom driven by two beams of light has been theoretically predicted by Narducci et al [40], and a large number of experiments subsequently observed this phenomenon [41][42][43][44][45]. Applications of the spectral line narrowing include laser spectroscopy [46] and quantum sensing [47].…”
Section: Introductionmentioning
confidence: 95%
“…It arouses our interest. As early as 1990, the sub-natural linewidth in the spontaneous emission spectrum of a threelevel atom driven by two beams of light has been theoretically predicted by Narducci et al [40], and a large number of experiments subsequently observed this phenomenon [41][42][43][44][45]. Applications of the spectral line narrowing include laser spectroscopy [46] and quantum sensing [47].…”
Section: Introductionmentioning
confidence: 95%